PENGARUH DEMINERALISASI BATUBARA DENGAN PENAMBAHAN ADSORBEN SEKAM PADI TERHADAP POTENSI PEMBENTUKAN SLAGGING DAN FOULING - Sekar Azizah Wardah; Pratama, Irham (UIR Press, 2025)
This study aims to evaluate the effect of coal demineralization with the addition of rice husk adsorbent on the potential formation of slagging and fouling. The demineralization process was carried out by mixing coal and rice husk at various ratios (100:0 to 50:50), followed by analysis of total sulfur content using a LECO S832 DR Sulfur Analyzer and ash mineral composition using an AAS Varian AA240 SF. The results showed that adding rice husk significantly reduced the sulfur content of coal by up to 50% and decreased the slagging (Rs) and fouling (Rf) indices from medium/high to low categories. Increasing the rice husk ratio also raised SiO₂ content while reducing Al₂O₃, Fe₂O₃, CaO, and MgO concentrations. It is concluded that rice husk is an effective adsorbent for coal demineralization, capable of lowering sulfur content and mitigating slagging and fouling potential, thereby improving combustion efficiency and reliability in boiler systems.